Modern software engineering methodologies for mobile and cloud environments - Cruz, Antonio Miguel Rosado da, 1970-; Paiva, Sara, 1979- (Information Science Reference, 2016)
"This book investigates emergent trends and research on innovative software platforms in mobile and cloud computing, featuring state-of-the-art software engineering methods, as well as new techniques being utilized in the field"- Resumé vydavatele
Keywords: cloud computing; mobilní komunikační zařízení; softwarové inženýrství; mobile communication devices; software engineering; kolektivní monografie; elektronické knihy; collective monographs; electronic books